Learning monetary policy strategies at the effective lower bound with sudden surprises - Spencer David Krane; Leonardo Melosi; Matthias Rottner (Deutsche Bundesbank, 2023)
We examine how private sector agents might learn a new monetary strategy that is adopted while at the ELB. Little can be discovered until the economy improves enough that rates would be near liftoff under the old strategy. Recessionary shocks would thus delay learning while large inflationary shocks could outright stop it and so inhibit the ability of the new strategy to address future ELB episodes. The central bank can offset some of the inflation-induced learning loss by deviating from its new strategy, but this decision comes at the cost of higher near-term inflation and greater uncertainty about monetary policy.
Keywords: E52; C63; E31; 330; New framework; central bank's communications; deflationary bias; asymmetric average inflation targeting; imperfect credibility; liftoff; Bayesian learning